Economic development - Galbraith, John Kenneth (Harvard University Press, 1964)
This book has the compiled lectures the famed economist, John Kenneth Galbraith, gave in India in 1961. He comments on how the US version of capitalism seem to succeed with the help of government, even as it would never admit such a 'socialist' dependency on it; implying it couldn't succeed without it. Galbraith also says the energies of man's effort to launch himself across space should not neglect "..a second, less grand, less costly, but not perhaps less important..effort.. to improve the position of those who will stay behind."